A single nuclear transcriptomic characterisation of mechanisms responsible for impaired angiogenesis and blood-brain barrier function in Alzheimer’s disease - Stergios Tsartsalis; Hannah Sleven; Nurun Fancy; Frank Wessely; Amy M. Smith; Nanet Willumsen; To Ka Dorcas Cheung; Michal J. Rokicki; Vicky Chau; Eseoghene Ifie; Combiz Khozoie; Olaf Ansorge; et al. (Nature Communications, 2024)
Abstract Brain perfusion and blood-brain barrier (BBB) integrity are reduced early in Alzheimer’s disease (AD). We performed single nucleus RNA sequencing of vascular cells isolated from AD and non-diseased control brains to characterise pathological transcriptional signatures responsible for this. We show that endothelial cells (EC) are enriched for expression of genes associated with susceptibility to AD. Increased β-amyloid is associated with BBB impairment and a dysfunctional angiogenic response related to a failure of increased pro-angiogenic HIF1A to increased VEGFA signalling to EC. This is associated with vascular inflammatory activation, EC senescence and apoptosis. Our genomic dissection of vascular cell risk gene enrichment provides evidence for a role of EC pathology in AD and suggests that reducing vascular inflammatory activation and restoring effective angiogenesis could reduce vascular dysfunction contributing to the genesis or progression of early AD.